A Method to Estimate Mean Lying Rates and Their Full Distribution - Ellen Garbarino; Robert Slonim; Marie Claire Villeval (Institute of Labor Economics (IZA), 2018)
Studying the likelihood that individuals cheat requires a valid statistical measure of dishonesty. We develop an easy empirical method to measure and compare lying behavior within and across studies to correct for sampling errors. This method estimates the full distribution of lying when agents privately observe the outcome of a random process (e.g., die roll) and can misreport what they observed. It provides a precise estimate of the mean and confidence interval (offering lower and upper bounds on the proportion of people lying) over the full distribution, allowing for a vast range of statistical inferences not generally available with existing methods.
Keywords: C91; C81; D03; 330; sampling errors; econometric estimation; lying; dishonesty; experimental economics